Myrtus communis L. Essential Oil Exhibits Antiviral Activity against Coronaviruses - Dar-Yin Li; Matthew G. Donadu; Taylor Shue; Georgios Dangas; Antonis Athanasiadis; Shuiyun Lan; Xin Wen; Basem Battah; Stefania Zanetti; Vittorio Mazzarello; Stefan G. Sarafianos; Marco Ferrari; et al. (MDPI AG, 2024)
Human coronaviruses are a continuous threat to the human population and have limited antiviral treatments, and the recent COVID-19 pandemic sparked interest in finding new antiviral strategies, such as natural products, to combat emerging coronaviruses. Rapid efforts in the scientific community to identify effective antiviral agents for coronaviruses remain a focus to minimize mortalities and global setbacks. In this study, an essential oil derived from Myrtus communis L. (MEO) is effective against HCoV-229E and HCoV-OC43 virus infections in comparison to two FDA-approved drugs, Remdesivir and Nirmatrelvir. Gas-chromatography and mass spectrometry were used to identify the chemical composition of MEO. Slight antioxidant activity was observed in MEO, indicating a role in oxidative stress. A dose-response curve measuring the EC50 indicates a high potency against HCoV-229E and HCoV-OC43 virus infections on Huh7.5 cells with low cytotoxicity using a PrestoBlue cell viability assay. Our findings demonstrate that MEO exhibits potent antiviral activity against HCoV-229E and HCoV-OC43 on Huh7.5 cells within a low-cytotoxicity range, but not on SARS-CoV-2. Artificial bacterial chromosome plasmids that expressed SARS-CoV-2 used for replicon-to determine viral replication and viral assembly/egress on HEK293T/17 cells-and virus-like particles on Huh7.5-AT cells-to determine viral entry and assembly/egress-showed no antiviral activity with MEO in comparison to Remdesivir. This study reveals the potential effectiveness of MEO as an alternative natural remedy to treat human coronaviruses and a potential antiviral agent for future coronavirus infections.